Analysis of human physical vulnerability using static equilibrium techniques of a Hazard flood for the determination of unsafe areas in the city of Catacaos – Piura, Peru. Issue 1 (December 2021) - Carrizales, J A; Rodas, M C; Castillo, L F
Abstract: Heavy rains and El Niño phenomenon are recurring natural phenomena at a national level. These can cause floods due to the overflowing of rivers, which, when close to cities, can cause both human and material losses. The district of Catacaos, located in the city of Piura, was the one with the highest number of injuries due to the flood caused by El Niño phenomenon in 2017. This phenomenon causes a large amounts of rainfalls due to the presence of abnormally warm waters along the northern coast of Peru [1]. It is for this reason that the need arose to carry out an analysis of the physical vulnerability due to instability of people through static equilibrium, in said district, in order to present maps of unsafe areas in the face of this phenomenon. In this investigation, flood hazard maps are generated simulating the one presented in 2017, using 2D hydraulic modeling. For the generation of vulnerability curves, the instability analysis is performed by moment and drag force. Finally, maps with unsafe areas are made using ArcGis software. Where the results obtained indicate that 29.37% of the city was flooded. Likewise, the vulnerability maps generated show us that women and men over 18 years of age in the city of Catacaos would be vulnerable to dragging and overturning in the face of floods in 16.54% and 13.21%, respectively, of the total studied area. This information will be useful for the development of future evacuation plans during floods, carried out by national entities.